Determination of optimum nitrogen application rates in Zhejiang Province, China, based on rice yields and ecological security - Yan LI; Yi CHEN; Chun-yan WU; Xu TANG; Xiao-jiang JI (Journal of Integrative Agriculture, 2015)
Excessive nitrogen (N) fertilization in intensive agricultural areas such as the plain region of South China has resulted in low nitrogen use efficiency and serious environmental problems. To determine the optimum N application rate, grain yield, apparent nitrogen recovery efficiency (ANRE), apparent N loss, and ammonium (NH3) volatilization under different N application rates in the three years from 2012 to 2014 were studied. The results showed that the relationship between grain yields and N application rate in the three years were well fitted by quadratic equations. When N application rate reached 197 kg ha−1 in 2012, 199 kg ha−1 in 2013 and 196 kg ha−1 in 2014, the plateau of the grain yields appeared. With the increase of N application rate, the ANRE for rice decreased which could be expressed with sigmoidal equation; when N application rate was 305 kg ha−1 in 2012, 275 kg ha−1 in 2013 and 312 kg ha−1 in 2014, the curves of ANRE appeared turing points. Besides, the relationship between soil Nresidual and N application rate was fitted by the quadratic equation and the maximums of soil Nresidual were reached in the three years with the N application rate of 206, 244 and 170 kg ha−1, respectively. Statistical analysis indicated that NH3 volatilization and apparent N loss in three years all increased with the increasing N application rate. When the amount of NH3 volatilization increased to 11.6 kg N ha−1 in 2012, 40.5 kg N ha−1 in 2013 and 57.0 kg N ha−1 in 2014, the apparent N loss in the three years had obvious increase. To determine the optimum N application rate, the average N application on the plateau of the grain yield was considered as the lower limit while the average N application rate at the turning points of ANRE, the residual N in soil and apparent N loss was taken as the upper limit. According to the results in three years, the optimum N application rate for rice in Zhejiang was 197–255 kg ha−1.